STIMULASI PENGGUNAAN MEDIA GAME DIGITAL DALAM MENGASAH KEMAMPUAN BERHITUNG SISWA KELAS I SDN 38/IX JAMBI KECIL - Novi Safitriana Risqi; Sri Indriani Harianja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of technology in the digital era has brought significant changes in the world of education, especially in learning media. This study aims to explore the use of game-based digital learning media to improve the counting skills of grade I students of SDN 38/IX Jambi Kecil. The media used, “Math Garden Adventure,” was designed with three interactive menus: counting fruits, counting vegetables, and fruit-vegetable market. The research method used was qualitative, with three stages: initial observation, digital media implementation, and final observation. The results showed that the digital game media was able to improve students' understanding of addition and subtraction counting operations. Students' enthusiasm increased significantly, as seen from the increase in the number of students who could solve the problems independently. This media not only makes learning more interesting and interactive but also helps students understand math concepts effectively. This research confirms the importance of teachers' adaptation to technological developments in creating innovative and relevant learning to support students' needs.